2008
DOI: 10.1002/chem.200800595
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic Iron‐Catalyzed Asymmetric Epoxidation of Aromatic Alkenes by Using Hydrogen Peroxide

Abstract: A novel and general biomimetic non-heme Fe-catalyzed asymmetric epoxidation of aromatic alkenes by using hydrogen peroxide is reported herein. The catalyst consists of ferric chloride hexahydrate (FeCl(3)6 H(2)O), pyridine-2,6-dicarboxylic acid (H(2)(pydic)), and readily accessible chiral N-arenesulfonyl-N'-benzyl-substituted ethylenediamine ligands. The asymmetric epoxidation of styrenes with this system gave high conversions but poor enantiomeric excesses (ee), whereas larger alkenes gave high conversions an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
60
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(63 citation statements)
references
References 51 publications
2
60
0
1
Order By: Relevance
“…[150] Thel atter radicals (HOC and the oxyl radical of cyclohexenol) were trapped as DMPO adducts (vide supra)a nd identified by EPR, following the method describedb yB eller. [82] Reaction of the complexes with H 2 O 2 wass tudied by UV-Vis and EPR spectroscopy and the formation of (L10)FeOOH and (L11)FeOOH intermediates was proposed. Such low-spin intermediates have been found to slowly build up and then decay in the presence of the substrates.…”
Section: Other Imine-based Iron Complexesmentioning
confidence: 99%
See 1 more Smart Citation
“…[150] Thel atter radicals (HOC and the oxyl radical of cyclohexenol) were trapped as DMPO adducts (vide supra)a nd identified by EPR, following the method describedb yB eller. [82] Reaction of the complexes with H 2 O 2 wass tudied by UV-Vis and EPR spectroscopy and the formation of (L10)FeOOH and (L11)FeOOH intermediates was proposed. Such low-spin intermediates have been found to slowly build up and then decay in the presence of the substrates.…”
Section: Other Imine-based Iron Complexesmentioning
confidence: 99%
“…[81] According to the protocold eveloped by Beller et al, [82] trace amounts of the desired radical trap are added to the reaction mixture under catalytic conditions.T he solution is rapidly freezequenched at 77 Ka nd analyzed by EPR spectroscopy.…”
Section: Use Of Radical Trapsmentioning
confidence: 99%
“…Of a selection of alkenes screened, the substrate with a 2-naphthyl group was oxidised in the highest ee -which could be raised to 97% through the use of 5 additional catalyst. In detailed follow-up studies, 66 a comparison of TsDPEN derivatives was made, and the effect of catalyst loading was studied; above 12 mol% ligand gave little improvement to the yield and a reduction in ee was observed. 10 Detailed mechanistic studies revealed that several iron complexes form within the mixture, several of which were identified by ESIMS.…”
Section: ) Oxidation Reactions Of Alkenesmentioning
confidence: 99%
“…This method afforded the correspongding epoxides in good to excellent yields. [22][23][24][25][26] Recently, they also reported a simpler system that uses imidazole derivatives, rather than dipicolinic acid and amines, 27,28) as ligands. However, the reactivity of this system was moderate, and the ligands which resulted in relatively high yields had to be synthesized ad hoc before use because of commercial inavailability.…”
mentioning
confidence: 99%